Penilaian Kinerja Pelayanan Publik melalui Balanced Scorecard pada Kantor Camat Panai Tengah - Romy Wanda Pane; Nur Fadhilah Ahmad Hasibuan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The aim of this research is to find out how public services perform at the Panai Tengah District office. This research uses qualitative descriptive analysis. Data collection was carried out through interviews with personnel sub-division employees who handle the performance of Central Panai sub-district office employees. According to Creswell, J. W. Qualitative Research is research used to study human and social problems. Where researchers will report research results based on data views and data analysis reports obtained in the field, then described in a detailed research report. The research results show that the performance of public services at the Panai Tengah District office is not optimal. Where the results of the research show that the majority of employees at the Panai District office violate SOPs such as being late for work, resulting in the quality of service not being optimal. The limitation of this research is that the results obtained are difficult to generalize widely, because the research is only based on research studies at one sub-district office. So that future researchers can carry out more research in other sub-district offices, so that the research results can be widely generalized. Keyywords: Performance assessment, Balanced Scorecard, District office Panai Tengah